Association of Obesity With Health Literacy and Weight Perception Among Women Merchants in Abidjan, Côte d'Ivoire: A Cross-Sectional Study - Rui Usui; Maki Aomori; Shogo Kanamori; Bi Tra Jamal Sehi; Setsuko Watabe (SLACK Incorporated, 2024)
Background: In Abidjan, Côte d'Ivoire's largest city, obesity rates among women are increasing, posing a major health challenge, especially for the working generation. Merchants represent 64.3% of working women and are a typical occupation for women with low- and middle-income. Health literacy is used to prevent and overcome chronic diseases and can be used as anti-obesity measures. Objective: The aim of this study was to examine the relationship between obesity, health literacy, and weight perception among women merchants in Abidjan. Methods: In this cross-sectional study, we conducted a complete enumeration survey among women merchants in a market in Abidjan from December 2020 to December 2021. In addition to anthropometric measurements, structured face-to-face interviews were conducted. The participants were asked about their weight perception, weight management behaviors, and sociodemographic attributes. They also responded to the Health Literacy Questionnaire (HLQ). Data were tabulated using descriptive statistics, and multiple logistic regression analysis was performed to examine obesity's association with HLQ scales, weight perception, and weight management behaviors. Key Results: Of the 873 participants, 259 (29.7%) were obese; 82% of them underestimated their weight. Obesity was associated with a higher rate of HLQ1 (Feeling understood and supported by health care providers) (odds ratio [OR] = 2.926, confidence interval [CI]:1.450-5.901, p = .03), a lower score of HLQ3 (Actively managing my health) (OR = 0.343, CI:0.165-0.716, p = 0.004), a lower rate of accurate weight perception (OR = 0.145, CI: 0.093-0.224, p < .001), and a lower rate of eating at least three meals per day (OR = 0.401, CI:0.260-0.617, p < .001). Conclusions: Findings from this study of Abidjan women merchants include obese participants' lack of a proactive attitude toward personal health management, and the association of factors such as inaccurate weight perception and eating fewer than three meals per day with obesity. These finding have important implications for future anti-obesity measures. [HLRP: Health Literacy Research and Practice. 2024;8(2):e102-e112.]